PROFILE OF PARTICIPANTS OF RUNNING EVENTS IN KOSZALIN ON THE EXAMPLE OF FOREST FIVE RUNS (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article is empirical. The aim of the article is to describe the cyclical running events held in Koszalin under a common name Forest Five and presentation of the runner's profile, its participant. This profile was created on the basis of runners' opinion collected during selected Forest Five runs held in 2019. Based on the research results obtained, the characteristics of the participant of the Forest Five can be outlined. It is a person in the prime of life, usually a man, a resident of Koszalin, with different running experience, taking care of his health and pleasure, developing a passion for running and appreciating the company and atmosphere of the running event.
Keywords: running, running events, Forest Five, runner profile